2012
DOI: 10.1038/ijo.2012.125
|View full text |Cite
|
Sign up to set email alerts
|

Obesity enhanced respiratory health effects of ambient air pollution in Chinese children: the Seven Northeastern Cities study

Abstract: OBJECTIVE: Experimental data suggest that obesity enhances the effects of ambient air pollutants on exacerbation of asthma; however, there is little supporting epidemiological evidence. The aim of present study is to evaluate whether obesity modifies the association between ambient air pollution and respiratory symptoms and asthma in children. METHODS: In Northeast China, 30 056 children aged 2-14 years were selected from 25 districts of seven cities. Parents of the children completed questionnaires that chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…Obese people have increased airway reactivity and respiratory symptoms in response to ozone (71,72), and increases in IL-1b in induced sputum in response to ozone are directly correlated with BMI (73). Increased responses to ozone are also reported in different models of obese mice (19,74,75).…”
Section: Irritant-and Pollutioninduced Asthma In Obesitymentioning
confidence: 74%
“…Obese people have increased airway reactivity and respiratory symptoms in response to ozone (71,72), and increases in IL-1b in induced sputum in response to ozone are directly correlated with BMI (73). Increased responses to ozone are also reported in different models of obese mice (19,74,75).…”
Section: Irritant-and Pollutioninduced Asthma In Obesitymentioning
confidence: 74%
“…They reported significant interactions between a change in PM 10 concentration and BMI; after a decrease in PM 10 concentration, the annual rates of decline in lung function were smaller in the groups with low or normal BMI compared with those defined as obese according to BMI. Dong et al 13 found that the risks for asthma and respiratory symptoms including cough were greater in obese children than in normal weight children. In particular, the interaction effects with obesity on cough and phlegm were significant for NO 2 and PM 10 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous reports have shown significant synergistic effects of obesity and exposure to ambient air pollutants such as nitrogen dioxide (NO 2 ) and PM 10 content on lung function using an indirect measurement of obesity including body mass index (BMI), 6,13,14 accurate quantitative measurement of adipose tissue mass by computed tomography (CT) is needed to understand the plausible mechanisms between adipose tissue and air pollution in lung function. However, to our knowledge, no studies have investigated whether there is an additive effect of fat accumulation in adipose tissue on the relationship between ambient air pollution and lung function.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, measured concentrations were more likely to reflect the background pollution level in a city rather than those from local sources. In line with prior research (Dong et al, 2013a(Dong et al, , 2013b, these measurements were used as proxies for long-term exposure for the participants. Measurements adhered closely to the methodological standards outlined by the State Environmental Protection Administration of China.…”
Section: Ambient Air Pollutionmentioning
confidence: 99%
“…We have reported air pollution data collection elsewhere (Dong et al, 2013a(Dong et al, , 2013b. Briefly, during the investigation, each district had only one municipal air monitoring station.…”
Section: Ambient Air Pollutionmentioning
confidence: 99%